CFD Investigation of the Effects of Split Main Fuel Injection Parameters on Combustion and Emissions in a Light-Duty Diesel Engine - Ng, H. K.; Shayler, P. J. (2006)
The paper outlines CFD investigations on the combustion and emission effects of the fuel injection strategies in a direct injection diesel engine fitted with a high pressure common rail fuel injection system. Strategies using a split main injection has been explored, with the variables of interest including the ratio of the first to second part of the main, the separation between these and the timing of the start of main injection. Exhaust gas recirculation rate was a fourth variable. The main influence of these 4 parameters on the nature of the combustion, and the resulting NO and soot emissions is characterised. Model validation has been based on comparisons with experimental data for heat release rate and engine-out emissions values. Simulations have been performed under typical part-load operating conditions, where the temporal and spatial developments of combustion/emissions processes are mapped out.